SURVEI STATUS GROSS MOTOR SKILL PADA SISWA KELAS RENDAH DI SEKOLAH DASAR NEGERI SE KECAMATAN PUJON KABUPATEN MALANG - Kurniawan, Faisal Harifko; Wiguno, Lokananta Teguh Hari; Darmawan, Arief (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2024)
This research aims to examine and understand the level of gross motor skills in students in the lower classes of A-accredited public elementary schools in Pujon District, Malang Regency. The method applied in this study is a quantitative descriptive survey method. Samples were taken by applying the proportionate stratified random sampling technique. Then to measure gross motor skills using the TGMD 3 instrument. The gross motor skills of students in grades 1, 2 and 3 with the highest percentage were 73.86% and with a total of 113 students reaching the average category. So it can be concluded that the level of gross motor skills of low class students in A-accredited public elementary schools in Pujon District, Malang Regency is included in the average group.